Biotechnological production of natural pigments for textile dyeing - Basto, Bruna; da Silva, Nuno R.; Teixeira, José A.; Silvério, Sara C. (Frontiers in Microbiology, 2025)
Global markets, including the pigments sector, have been significantly influenced by the adoption of novel circular bioeconomy policies and increasing concerns about sustainable practices. The natural pigments market is expected to grow considerably due to policies promoting renewable resources and reducing environmental impact. Natural pigments, particularly fungi-derived ones, are increasingly favored for their biodegradability, non-toxicity, and additional biological properties, offering a safer alternative to synthetic dyes. This shift is particularly notable in the textile industry, where concerns over synthetic dyes’ environmental and health impacts have prompted the search for sustainable coloring solutions. This work demonstrates the suitability of agro-industrial byproducts, namely cheese whey and corn steep liquor, as alternative culture medium components for producing natural pigments by Penicillium brevicompactum. Furthermore, using corncob as a support for fungal immobilization, under submerged fermentation conditions, resulted in high pigment yields, even when the culture medium was composed of only agro-industrial byproducts. Two different natural pigments’ mixtures were successfully used to dye cotton and linen fabrics, highlighting P. brevicompactum pigments’ potential as environmentally acceptable alternatives to synthetic dyes. Overall, this work describes, for the first time, the sustainable production of natural pigments and their potential for textile industry applications.